Design and Implementation of Update Script in the IoT-Based Smart Indoor Farming System Module at PT Inastek Using Over-the-Air Programming - Aditya, Tomi; Dhewa, Oktaf Agni (Media of Computer Science, 2024)
Extreme climate change significantly impacts Indonesia’s agricultural sector, a country with a large agrarian economy. Reduced crop productivity and in- creased risk of pest infestations threaten national food security. This study aims to develop a smart indoor farming system based on the Internet of Things (IoT) to enhance agricultural resilience and competitiveness through efficient technology. The method involves designing a system that integrates hardware and software, applying Over-The-Air (OTA) technology to update firmware on the ESP32 microcontroller. The system includes sensors, actuators, and a Human Machine Interface (HMI) that allows real-time monitoring and con- trol of plant growth conditions. Testing and validation were carried out to ensure the system’s reliability and stability. The results show that the in- tegration of OTA technology into the smart indoor farming system enables efficient firmware management, reducing the need for physical intervention, and improving flexibility in system maintenance. This system enhances the efficiency of managing plant growth in indoor environments and supports con- tinuous operational adjustments to dynamic conditions.